Inovasi Media Pembelajaran Menggunakan AR (Augmented Reality) pada Materi Sistem Pencernaan: (Learning Media Innovation Using Augmented Reality on Digestive System Material) - Resti, Novita; Ridwan, Ridwan; Palupy, Rizka Trian; Riandi, Riandi (BIODIK, 2024)
The learning process is a communication that involves teachers, students and subject matter. Learning media is needed to clarify the material and facilitate effective interaction between teachers and students. Along with the development of technology, Augmented Reality (AR) is one of the potential learning media. AR is able to improve concept understanding with interesting and interactive 3D visualizations, such as in the human digestive system material in the Merdeka Phase F class XI curriculum. However, AR also has drawbacks such as the lack of immediate feedback and distraction for students. To overcome this, innovation is needed, for example by integrating audio and video in AR media, thus providing a more thorough and effective learning experience. This innovation can support active and collaborative inquiry-based learning, enrich student understanding, as well as facilitate dynamic formative assessment. With collaboration between educators, technology developers and policy makers, the challenges of AR implementation can be overcome. The integration of this technology in education has the potential to improve the quality of learning and the development of 21st century skills such as creativity and problem solving. Key words: media innovation, augmented reality, biology learning